Challenges in the Implementation of Intellectual Property Rights as Fiduciary Collateral in Indonesia - Panjaitan, Haposan; Arifardahni, Yoyo; Samosir, Tetti (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
Intellectual property rights (IPRs) refer to legal entitlements from intellectual and creative efforts, resulting in intangible assets. Copyright, as a specific form of IPR, is classified as an intangible movable property and is legally recognized as a potential object of fiduciary security in Indonesia. Despite regulatory developments—particularly Government Regulation No. 24 of 2022 concerning the creative economy—the practical implementation of IPR-based collateral remains constrained by the absence of standardized valuation mechanisms, institutional readiness, and legal certainty. This study employs a normative juridical method grounded in statutory and doctrinal analysis to examine the valuation framework of copyrights as fiduciary collateral and the legal role of public notaries and certified appraisers. The findings reveal that regulatory inconsistencies and the lack of operational guidelines inhibit financial institutions from accepting copyright as a credible collateral asset. Moreover, the role of notaries is pivotal in affirming ownership validity and ensuring the legal enforceability of fiduciary deeds involving intellectual property.